UPAYA PREVENTIF PENYEBARAN TUBERKULOSIS MELALUI PEMBERDAYAAN MASYARAKAT DALAM MENGOLAH DAUN KELOR SEBAGAI SPRAY DESINFEKTAN DI RT 02 RW 02 KELURAHAN PASIRKALIKI, KECAMATAN CIMAHI UTARA, KOTA CIMAHI - Abror, Yogi Khoirul; Merdekawati, Fusvita; Juliastuti, Aditya (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2024)
Tuberculosis (TB) remains a global health issue, with Indonesia ranking second worldwide in TB cases. The high incidence of TB is partly due to its ease of transmission via droplets in densely populated areas. One preventive measure is improving environmental hygiene through disinfectants. However, chemical-based disinfectants often leave residues, prompting the need for natural alternatives, such as Moringa oleifera leaves, which exhibit antibacterial potential. This community service activity aimed to enhance the knowledge and skills of Posyandu Mawar 01 and 02 cadres in RT 02 RW 02, Pasirkaliki Village, Cimahi Utara Sub-district, on processing moringa leaves into disinfectant sprays to prevent TB transmission. The program included preparation, education, mentoring, pre-tests, and post-tests. Supporting materials such as presentations, leaflets, videos, and moringa-based disinfectant spray products were distributed to cadres for further education. The results showed a 42% increase in cadres' knowledge, with an average post-test score of 85 compared to a pre-test score of 60. This activity effectively improved cadres' understanding of TB prevention using natural materials. It is hoped that similar activities will be conducted regularly to raise community awareness and capacity in TB control.